Reform of secondary military educational institutions in Russia and its fate (1917–1918) - Lukashevich, Andrei M. (Journal of the Belarusian State University. History, 2023)
The article, through the prism of a value approach, examines the reform of secondary military educational institutions (cadet corps) in Russia, carried out under the Provisional Government. The preparatory measures, the creation and activities of the commission for the reorganisation of military educational institutions under the leadership of general Z. A. Maksheev are revealed. It is noted that in March – July 1917, the commission did a lot of work to reorganise the military school on a broad democratic basis. From the 1917/18 academic year, access to the cadet corps was open to children of all classes. In order to create equal conditions for admission to state support, the requirements for exams were lowered, and instead of a competition, a ballot system was introduced. In the course of the reform, the cadet corps were transformed into gymnasiums of the military department and acquired the character of general educational institutions (ranks and drill classes were canceled, weapons and banners were confiscated, and civilians were allowed to fill all positions). Measures were taken to simplify the life of pupils and to serve their own needs, the creation of student organisations was allowed. The management of gymnasiums was established on the principle of trust in the staff (most issues were decided by the pedagogical council). It is concluded that the coming to power in October 1917 of the Bolsheviks led to the rejection of the reform. Since the majority of the cadet community, formed under the imperial government and brought up in a monarchical spirit, did not recognise the Soviet government, the gymnasiums of the military department were abolished in July 1918.